Costa Rica Inequality: A Distributive Analysis of the top Incomes (2010-2019) - Ramírez Cardoza, Lorenzo (2025)
Parting from the combined analysis of surveys, National Accounts and taxing data, this article documents a greater increase in inequality in Costa Rica than the one reported from the exclusive use of household surveys.  Thus, the increase in inequality registered in the first years of the 21st century would be even greater.  It specifically presents a distributive analysis from the "top income shares" approach, with the measurements of the 1 %, 0,5 % and 0,1 % and it observes the effect of their level of concentration on inequality measured by the Gini coefficient based on surveys.  The analysis presented makes a methodological and empirical contribution by improving the validity of income distribution studies and also by confirming a trajectory of increasing inequality for Costa Rica, respectively.